2020
DOI: 10.1108/hff-02-2020-0095
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of micropolar hybrid ferrofluid flow over a vertical plate by considering various base fluid and nanoparticle shape factor

Abstract: Purpose The purpose of this paper is to investigate micropolar magnetohydrodynamics (MHD) fluid flow passing over a vertical plate. Three different base fluids have been used that include water, ethylene glycol and ethylene glycol/water (50%–50%). Also, a nanoparticle was used in all of the base fluids. The effects of natural convection heat transfer and magnetic field have been taken into account. Design/methodology/approach The main purpose of solving the governing equations is to scrutinize the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…Some valuable studies on the application of hybrid nanofluid are found in the studies reported in Ref. [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Some valuable studies on the application of hybrid nanofluid are found in the studies reported in Ref. [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Gholinia et al 2 considered various base fluids suspended by hybrid nanoparticles near a circular cylinder having a sinusoidal radius to study the heat transfer rate. Hosseinzadeh et al 3 analyzed the magnetohydrodynamic (MHD) flow of micropolar hybrid ferrofluid near an upright surface by considering several regular fluids and nanoparticle shape effect. A hydrothermal analysis of ethylene glycol based nanofluid flow inside a permeable container subject to Boussinesq‐Darcy law and magnetic effects was provided by Rostami et al 4 Ardahaie et al 5 scrutinized the impacts of supplemented nanoparticles on magnetized transport of blood through a porous blood vessel.…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of nanomaterials subject to different aspects of flow parameters are discussed and described graphically. Some significant research on fluid flow against various geometries are listed in References [23][24][25][26][27][28][29][30][31][32][33][34][35][36]…”
Section: Introductionmentioning
confidence: 99%